2017
DOI: 10.1055/s-0042-124502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Contrast-Enhanced Ultrasound in the Pediatric Work-Up of Focal Liver Lesions and Blunt Abdominal Trauma: A Systematic Review

Abstract: In pediatrics ultrasound has long been viewed more favorably than imaging that exposes patients to radiation and iodinated contrast or requires sedation. It is child-friendly and diagnostic capabilities have been improved with the advent of contrast-enhanced ultrasound (CEUS). The application of CEUS is indeed promising. However, no ultrasound contrast agent manufactured today is registered for pediatric use in Europe. The contrast agent SonoVue? has recently been approved by the FDA under the name of Lumason?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…A residual viable tumor can be detected during the RFA session using CEUS. In addition, CEUS may allow visualization of immediate complications after RFA such as active bleeding, hemobilia, or segmental infarction of the liver [155]. For these reasons, CEUS may have the potential to reduce the number of CT examinations after RFA [156].…”
Section: Guidance Of Tumor Ablationmentioning
confidence: 99%
“…A residual viable tumor can be detected during the RFA session using CEUS. In addition, CEUS may allow visualization of immediate complications after RFA such as active bleeding, hemobilia, or segmental infarction of the liver [155]. For these reasons, CEUS may have the potential to reduce the number of CT examinations after RFA [156].…”
Section: Guidance Of Tumor Ablationmentioning
confidence: 99%
“…A recent meta-analysis of nine studies comparing CEUS to contrast-enhanced CT in adult blunt trauma patients showed excellent sensitivity for CEUS of 0.981 (95 % CI: 0.868-0.950) and a false-positive rate of 0.018 (95 % CI: 0.010-0.032) for identifying parenchymal injuries [61]. The accuracy of CEUS in adult trauma patients is close to the sensitivity and specificity of contrast-enhanced CT. CEUS seems to be especially relevant for the up to 37 % of pediatric trauma patients that have abdominal parenchymal injuries verified on CT [62,63] but did not show evidence of free abdominal fluid on conventional B-mode ultrasound. Here, in addition to avoiding routine exposure to ionizing radiation and sedation for the CT exam, CEUS achieves excellent accuracy in identifying solid organ injuries that frequently present without free abdominal fluid and has shown comparable accuracy to that of contrast-enhanced CT [64].…”
Section: Ganzkörper-computertomografie (Gkct)mentioning
confidence: 96%
“…The use of US with contrast is off label in pediatrics with the exception of investigation of focal liver lesions, approved by the Food and Drug Administration in 2016, and vesicoureteral reflux. 35 Off-label use is common in pediatrics given that many drugs are not separately tested in children. As long as US contrast is off label, it will require that parents and guardians be informed of the risk and benefits of contrast use and acquire informed consent before its use.…”
Section: Future Directions-the Use Of Contrast-enhanced Ultrasoundmentioning
confidence: 99%